Urgensi Pendidikan Tinggi dalam Perspektif Perempuan di Desa Anjir Pasar Lama Kabupaten Barito Kuala - Normala; Zulaikha, Siti (Prodi Sosiologi FISIP ULM, 2025)
The social construction within society reflects issues of gender-based discrimination, one of which is the unequal treatment of men and women in the field of education. This study aims to explore the urgency of higher education from women's perspectives and to understand the social construction of rural communities regarding higher education for women. The research was conducted in Anjir Pasar Lama Village, Barito Kuala Regency. A qualitative method with a case study approach was employed. Data were collected through observation, interviews, and documentation. Data analysis followed the interactive model of Miles and Huberman. The findings reveal that in Anjir Pasar Lama Village, there are two prevailing perspectives on higher education for women: some members of the community believe that higher education is very important for women, while others consider it less important. Factors contributing to the low level of higher education among women in the village include early marriage, economic conditions, and a lack of awareness about the importance of higher education for women. The most dominant factor is early marriage. The social construction within the community is shaped by three dialectical processes: internalization, objectivation, and externalization. In this context, gender discrimination in Anjir Pasar Lama Village includes the marginalization of women in education, subordination of women, gender stereotypes, and violence. However, the concept of a double burden is not found, as women are primarily confined to domestic roles.